2023
DOI: 10.3389/fnetp.2022.1007585
|View full text |Cite
|
Sign up to set email alerts
|

The role of pulse timing in cardiac defibrillation

Abstract: Life-threatening cardiac arrhythmias require immediate defibrillation. For state-of-the-art shock treatments, a high field strength is required to achieve a sufficient success rate for terminating the complex spiral wave (rotor) dynamics underlying cardiac fibrillation. However, such high energy shocks have many adverse side effects due to the large electric currents applied. In this study, we show, using 2D simulations based on the Fenton-Karma model, that also pulses of relatively low energy may terminate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Further optimisation of anti-fibrillation control may be achieved by proper timing of the application of the pulse sequence, as it has recently been shown that the timing of single-shock termination has a significant influence on the probability of success ( Ji et al, 2017 ; Steyer et al, 2023 ).…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further optimisation of anti-fibrillation control may be achieved by proper timing of the application of the pulse sequence, as it has recently been shown that the timing of single-shock termination has a significant influence on the probability of success ( Ji et al, 2017 ; Steyer et al, 2023 ).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Progress has also been been made combining experimental data with numerical modelling, for example, for studying spatiotemporal alternans patterns of cardiac excitation ( Loppini et al, 2022 ). Recent numerical studies have shown that pulse timing is crucial for termination success ( Steyer et al, 2023 ). Furthermore, chaotic cardiac arrhythmias may exhibit self-termination ( Rappel et al, 2022 ), a phenomenon also seen with chaotic transients in generic excitable media ( Lilienkamp et al, 2017 ; Lilienkamp and Parlitz, 2018 ; Aron et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Exemplary snapshots of the transmembrane potential V m during spiral wave chaos are shown in Figure 1 for each model, respectively. As done in previous publications on pacing protocols, we also neglect the influence of the fibre orientation in the myocardium, assume absence of scar tissue and except for the MSA model, healthy electrophysiological behaviour of the ion channels within the myocardium ( Trayanova, 2006 ; Janardhan et al, 2014 ; Buran et al, 2017 ; Hornung et al, 2017 ; Lilienkamp and Parlitz, 2020 ; Lilienkamp et al, 2022a ; Lilienkamp et al, 2022b ; DeTal et al, 2022 ; Steyer et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…During the pacing process, the dynamics of the system is neglected, as the predetermined pulse frequencies are kept fix. However, Steyer et al showed that the exact timing of a single pulse plays a major role for a successful termination of a chaotic state ( Steyer et al, 2023 ). Additionally, the accuracy of the calculated pulse frequencies is inherently limited by the time period for which the system is observed prior to pacing ( B Traykov et al, 2012 ), as ADP and EquiDist are based on the frequency spectrum of the underlying dynamics and, respectively, its dominant frequency.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation